2012
DOI: 10.1111/j.1365-2885.2012.01397.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of tildipirosin in porcine plasma, lung tissue, and bronchial fluid and effects of test conditions on in vitro activity against reference strains and field isolates of Actinobacillus pleuropneumoniae

Abstract: Rose, M, Menge, M, Bohland, C, Zschiesche, E, Wilhelm, C, Kilp, S, Metz, W, Allan, M, Röpke, R, Nürnberger, M Pharmacokinetics of tildipirosin in porcine plasma, lung tissue, and bronchial fluid and effects of test conditions on in vitro activity against reference strains and field isolates of Actinobacillus pleuropneumoniae. J. vet. Pharmacol. Therap. 36, 140–153. The pharmacokinetics of tildipirosin (Zuprevo® 40 mg/mL solution for injection for pigs), a novel 16‐membered‐ring macrolide for the treatment for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
76
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(97 citation statements)
references
References 28 publications
(46 reference statements)
12
76
1
Order By: Relevance
“…More recently, Rose et al . (Rose et al ., ) reported that, for the novel veterinary macrolide tildipirosin, the addition to broth of increasing amounts of serum (from 5 to 50%) progressively reduced the MIC for six bacterial species harvested from pigs. Interestingly, MIC ratios for pure broth:broth supplemented with 50% serum were highest for S. aureus (8‐64:1) and least for M. haemolytica (2‐4:1) and P. multocida (1–2:1).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Rose et al . (Rose et al ., ) reported that, for the novel veterinary macrolide tildipirosin, the addition to broth of increasing amounts of serum (from 5 to 50%) progressively reduced the MIC for six bacterial species harvested from pigs. Interestingly, MIC ratios for pure broth:broth supplemented with 50% serum were highest for S. aureus (8‐64:1) and least for M. haemolytica (2‐4:1) and P. multocida (1–2:1).…”
Section: Discussionmentioning
confidence: 99%
“…Almost without exception, TD, like most macrolides, has been classified as time‐dependent killing drugs and therefore is best described by the PK/PD parameter time above MIC ( T > MIC ) for newer macrolides appears to be the best correlate with therapeutic effect. For example, a previous study reported that MIC 90 of TD for Actinobacillus pleuropneumoniae in pigs was 2,000 ng/ml (Rose et al., ). The concentration of tildipirosin was approximately 100 times higher in porcine lung than plasma during days 1–14 after i.m.…”
Section: Plasma Pharmacokinetics Parameters After Single Im Adminismentioning
confidence: 99%
“…The concentration of tildipirosin was approximately 100 times higher in porcine lung than plasma during days 1–14 after i.m. administration (Rose et al., ). Although in the current study, the C max of TD (approximately 1,000 ng/ml) in canine plasma after 4 mg/kg i.m.…”
Section: Plasma Pharmacokinetics Parameters After Single Im Adminismentioning
confidence: 99%
“…Bacteria, such as Actinobacillus pleuropneumoniae, Pasteurella multocida, Haemophilus parasuis and Mycoplasma hyopneumoniae are major pathogens involved in swine respiratory disease (SRD). Escherichia coli on the other hand, is one of the most important causes of postweaning diarrhea in pigs (Fairbrother et al, 2005;Rose et al, 2013).…”
mentioning
confidence: 99%